2021
DOI: 10.1007/s00170-021-07059-6
|View full text |Cite
|
Sign up to set email alerts
|

A numerical approach for the modelling of forming limits in hot incremental forming of AZ31 magnesium alloy

Abstract: Magnesium alloys, because of their good specific material strength, can be considered attractive by different industry fields, as the aerospace and the automotive one. However, their use is limited by the poor formability at room temperature. In this research, a numerical approach is proposed in order to determine an analytical expression of material formability in hot incremental forming processes. The numerical model was developed using the commercial software ABAQUS/Explicit. The Johnson-Cook material model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…The relationship between the average recrystallization grain size (d) and the Zener-Hollomon parameter (Z) during dynamic recrystallization is given by -lnd= A + Bln Z. Based on the present TC-ECAE process with extrusion temperature 400℃,average accumulative strains, strain rates and Z parameters of the AZ61 increase with the development of TC-ECAE process [21][22][23]. It can be found that the accumulative strains increase with the extrusion advancing, so the grains will be re ned consequently.…”
Section: Pridiction Microstructure Evolutions During Tc-ecae Processmentioning
confidence: 99%
“…The relationship between the average recrystallization grain size (d) and the Zener-Hollomon parameter (Z) during dynamic recrystallization is given by -lnd= A + Bln Z. Based on the present TC-ECAE process with extrusion temperature 400℃,average accumulative strains, strain rates and Z parameters of the AZ61 increase with the development of TC-ECAE process [21][22][23]. It can be found that the accumulative strains increase with the extrusion advancing, so the grains will be re ned consequently.…”
Section: Pridiction Microstructure Evolutions During Tc-ecae Processmentioning
confidence: 99%
“…Thus, friction would not only in uence extruding forces, but also affect the temperature distribution of the extrusion die. The temperature of the die increases with increasing friction coe cients [23][24][25].…”
Section: Variation In the Temperature Eld During The Es Processmentioning
confidence: 99%
“…The authors taxonomize those techniques to attempt an automation of the processes to resemble the tools movements and ensure similar results in terms of material properties and components geometry. Campanella et al (2021) use numerical models to predict the formability of a magnesium alloy. An explicit formulation is used to predict the forming limit of the alloy.…”
Section: Previous Isf Studiesmentioning
confidence: 99%